An Analysis of Employment Relations in the Saree Chips Home Industry: Based on the Concept of Ijarah 'Ala Al-‘Amal - Delfira, Safna; Yusuf, Muhammad; Sholihin, Riadhus (MAQASIDI: Jurnal Syariah dan Hukum published by the Islamic Criminal Law Program of the Sharia and Islamic Economics Department at the Sekolah Tinggi Agama Islam Negeri Teungku Dirundeng Meulaboh, 2025)
This study examines the practice of employment relations in the Saree chip home industry, Aceh Besar, which shows a mismatch with the principles of ijarah ala al-‘amal contracts in Islamic economic law. The main issue identified is the unilateral termination of employment without any deliberation mechanism or opportunity for workers to defend themselves. Such termination occurs while the employment contract is still valid, resulting in injustice and contradicting the principle of worker protection in Islam. Another problem that arises is the absence of employer responsibility in the event of workplace accidents. Risky working conditions, combined with the use of equipment and machinery, increase the likelihood of accidents. However, workers receive no guarantees or responsibility from employers for incidents they experience. This phenomenon highlights the gap between the theory of ijarah ala al-‘amal contracts, which emphasize justice, the balance of rights and obligations, and worker protection, and the reality of practices in the field. This study uses a qualitative descriptive-analytical approach with observation and interview methods. The findings show that employment relations in practice remain informal, without clear written agreements, thereby creating opportunities for injustice. Normatively, ijarah ala al-‘amal contracts require contractual clarity, protection of workers’ rights, and employer responsibility for occupational risks. Therefore, there is a need to reconstruct the employment system in the Saree chip home industry to align more closely with sharia principles, particularly in terms of legal certainty, justice, and worker safety protection.